Vulvar Metastasis in Renal Cell Carcinoma: A Case Report Highlighting the Aggressive Nature of Clear Cell Renal Cell Carcinoma - Andreea Boiangiu; Ana-Maria Cioca; Gabriel-Petre Gorecki; Romina-Marina Sima; Liana Pleș; Marius-Bogdan Novac; Ionut-Simion Coman; Valentin-Titus Grigorean; Vasile Lungu; Mihai-Teodor Georgescu; George-Alexandru Filipescu (Current Oncology)
Vulvar cancer is one of the rarest gynecological malignancies. The development of this condition can be associated with either dysplasia linked to human papillomavirus (HPV), primarily affecting younger women, or vulvar dermatoses such as lichen sclerosus, which predominantly affect older women. Over the last decade, the incidence of vulvar cancer has risen by 0.6% annually, while the relative survival rate has declined. Although metastasis to the vulva is uncommon, it can occur, particularly from cancers in nearby organs such as the cervix, bladder, rectum, or anus. More rarely, metastases from breast cancer and renal cell carcinoma have been reported in the vulva. Vaginal metastases from clear cell renal carcinoma are especially rare. In this article, we present the case of a 56-year-old patient diagnosed with clear cell renal carcinoma, who came to our clinic with a lesion on the right labia, which was identified as a metastasis originating from the kidney. Given the rarity of genital metastases in renal cancer, such cases should be examined and discussed to encourage further research and studies.